TorakochirurgiaVATS lobectomy: first experiences - Żurek, Wojciech; Sternau, Adam; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Anatomical, videothoracoscopic lung resection (VATS) is a surgical technique performed in leading thoracic centres for treatment of primary early stage lung cancer and benign lung diseases. Early results of VATS lobectomies performed in 2009 at the Thoracic Surgery Department, Medical University of Gdańsk were analysed. Material and methods: The following variables were retrospectively analysed: gender, age, pre- and postoperative TNM, tumour type and localisation, number and reasons of conversions to open thoracotomy, duration of operation, drainage volume in 24 hours after the operation, postoperative pain, postoperative stay, histopathology, morbidity and mortality. Results: Initially 41 patients underwent surgery with an intention to complete VATS lobectomy. Conversion to conventional surgery happened in 8 cases due to dense adhesions (5 pts), hilar lymph node swelling (2 pts) and faulty stapler (1 pt). Finally, 33 patients (20 females) were analysed, with the mean age of 62.8 years (ranging from 39 to 79 years). Twenty seven cases of primary lung cancer, 1 case of metastatic breast cancer and 5 benign lesions were diagnosed postoperatively. The mean duration of lo-bectomy was 210 min (ranging from 150 min to 360 min) and the mean postoperative stay was 9.7 days. The morbidity rate was 24.2%. Perioperative mortality was 0%. Conclusions: VATS lobectomy is a safe procedure at the first stage of primary lung cancer. Early results are comparable to thoracotomy, including oncological criteria for lung cancer surgery. VATS lobectomy is less painful with better cosmetic results comparing to thoracotomy. The lack of specially designed instruments and staplers is a major disadvantage of videothoracoscopy.